Urgensi Penggunaan Tata Bahasa yang Baik dalam Berkomentar di Aplikasi Media Sosial Tiktok Terhadap Kesehatan Mental dan Pembentukan Karakter pada Siswa SMP dan SMA - Shintia Dwi Alika; Arinda Puspa Dewi; Izaz Rakha Anggara; Rahma Hayyu Shabrany; Satriya Yoga Madhasatya (Jurnal Paedagogy, 2022)
This study aims to describe the psychological impact of toxic language in the comment section and the urgency of using good language on TikTok relating to mental health and character development, especially for high school students. This study used a qualitative method for data analysis by involving high school students aged 12-17 years old. Moreover, it uses questionnaires using a Google form that is shared with the respondents using linked messages via WhatsApp messenger and adding additional data with some screenshots from TikTok for the data collection. The hermeneutic technique is also used for the data analytics technique. The results of this study indicated that junior high school students used the TikTok application more often than high school students. In addition, there were still many negative comments with toxic language found by middle and high school students on social media, especially on TikTok. It can affect the quality of their mental health and their character development. Thus, students should be able to apply filter culture before sharing and still need supervision from the surrounding environment, such as teachers and parents.